2020
DOI: 10.3389/fmicb.2020.01924
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and Persistence to Drugs: A Main Challenge in the Fight Against Mycobacterium tuberculosis

Abstract: The treatment of tuberculosis is extremely long. One of the reasons why Mycobacterium tuberculosis elimination from the organism takes so long is that in particular environmental conditions it can become tolerant to drugs and/or develop persisters able to survive killing even from very high drug concentrations. Tolerance develops in response to a harsh environment exposure encountered by bacteria during infection, mainly due to the action of the immune system, whereas persistence results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 88 publications
(124 reference statements)
0
45
0
Order By: Relevance
“…Intriguingly, we found that expression of CD11c in the host cell correlates inversely with the expression levels of hspx9::GFP (Fig. 4 Drug tolerance is defined as an increase in the survival times of bacterial cells toward a bactericidal drug without any change in the minimum inhibitory concentration and this phenomenon is frequently associated with a reduction of bacterial metabolism upon encountering specific environmental conditions (Boldrin et al, 2020). We had shown previously that the drug tolerance phenotype in Mtb can be induced through classical activation of macrophages in vitro and that nitrosative stress is the most potent single inducer of drug tolerance in Mtb in a murine infection in vivo (Liu et al, 2016).…”
Section: Expression Of the Surface Marker Cd11c Is Inversely Associated With Drug-tolerant Bacteriamentioning
confidence: 86%
“…Intriguingly, we found that expression of CD11c in the host cell correlates inversely with the expression levels of hspx9::GFP (Fig. 4 Drug tolerance is defined as an increase in the survival times of bacterial cells toward a bactericidal drug without any change in the minimum inhibitory concentration and this phenomenon is frequently associated with a reduction of bacterial metabolism upon encountering specific environmental conditions (Boldrin et al, 2020). We had shown previously that the drug tolerance phenotype in Mtb can be induced through classical activation of macrophages in vitro and that nitrosative stress is the most potent single inducer of drug tolerance in Mtb in a murine infection in vivo (Liu et al, 2016).…”
Section: Expression Of the Surface Marker Cd11c Is Inversely Associated With Drug-tolerant Bacteriamentioning
confidence: 86%
“…This frameshift mutations are particularly enriched in MDR- and XDR- M.tb strains, and suggest that variation in GlpK might contribute to the development of drug resistance. Thus, limited efficacy of current TB treatments suggests that heterogeneity of both host and mycobacterial physiologies in the different lung compartments during the different stages of the infection can influence the emergence of persisters and ultimately, increased drug resistance ( Warner and Mizrahi, 2006 ; Ben-Kahla and Al-Hajoj, 2016 ; Boldrin et al, 2020 ). Novel antimycobacterial drugs that target persisters populations are critical in order to shorten TB treatment and decrease the emergence and transmission of MDR- M.tb strains ( Zhang et al, 2012 ; Mandal et al, 2019 ).…”
Section: Origin and Evolution Of Drug Resistancementioning
confidence: 99%
“…Increases in SigE expression level are associated with exposure to heat shock, Sodium Dodecyl Sulfate (SDS, a detergent used to mimic surface stress) and antibiotics (such as isoniazid and vancomycin), [ 8 ]. In addition, SigE has been shown to have a major role in determining the amount of bacterial cells surviving prolonged drug treatment [ 9 ] and has been proposed as a switch for dormancy [ 10 ].…”
Section: Introductionmentioning
confidence: 99%